Implementation of a Real Time Analog Secure Image Communication System via a Chaotic Circuit - HANCERLİOGULLARI, Aybaba; MOHAMED EL HADAD, Khaled; KURT, Erol (Politeknik Dergisi, 2019)
A new secure image communication system has been designed and implemented based on a synchronized chaotic circuit. The new chaotic circuit, which has recently proposed by one of the authors contains a resistor, two inductors, and two diodes (i.e. R2L2D). The synchronization part operates with a master – slave configuration. In order to achieve the real-time communication, initially the analog master circuit has been implemented to generate chaotic sequences of numbers. Then, that analog tool has been transmitted to a computer via an analog/digital converter and a hidden image has been obtained. Besides, the slave circuit has also received a copy of that chaotic sequences in order to use it in subtraction process of image gray levels. The digital chaotic image has been transmitted to the slave circuit via a digital/analog converter with an efficient method and the decrypted image has been obtained in real-time. The advantage of that technique over the conversional ones is that it does not require any saved copy of the digital data, even for sending them in gray images to the receiver, since it is real-time. The conventional techniques use the stored and processed data and that can cause security problems in today’s advanced web media. Thus to send the encrypted image in a real-time device by using an analog chaotic equipment has certain security superiority. The analyses on the preliminary decrypted images proves that the process is efficient in time and secure.
Keywords: Engineering; Mühendislik; Secure communication; analog; chaotic circuit; image encryption; decryption